Variations in the linear and nonlinear refractive indices of chalcogenide glass thin films for photonic applications. (4th October 2019) - Musfir, P N; Nampoori, V P N; Thomas, Sheenu
Abstract: In this paper, we report the variations in linear and nonlinear refractive indices of Ge20 Ga5 Sb10 S65, Ge20 Ga5 Sb10 Se65, Ge25 Sb10 S65 and, Ge16 As24 S60 chalcogenide glass thin films. The linear refractive index (n) has been determined and analyzed by the Swanepoels method and the Wemple-DiDomenico model(WDD). The theoretical formulation by Fournier and Snitzer has been used to study the nonlinear refractive index (n2 ) which is compared with the modified Boling model. The compositional dependence of various parameters such as the optical band gap(Eg), linear refractive index, extinction coefficient(k), optical conductivity( σ ) and dielectric parameters( ε r, ε i ) was also analyzed. Results on variations of linear and nonlinear refractive indices are interpreted on the basis of the optical polarizability of the materials. The n2 of the prepared chalcogenide glass thin films are found to be two orders greater than that of pure and doped silica glasses which make them ideal candidates for all-optical networks.